Diffuse Alveolar Hemorrhage due to Acute Mitral Valve Regurgitation - Creticus P. Marak; Parijat S. Joy; Pragya Gupta; Yana Bukovskaya; Achuta K. Guddati (Case Reports in Pulmonology)
Diffuse alveolar hemorrhage (DAH) can be caused by several etiologies including vasculitis, drug exposure, anticoagulants, infections, mitral valve stenosis, and regurgitation. Chronic mitral valve regurgitation (MR) has been well documented as an etiological factor for DAH, but there have been only a few cases which have reported acute mitral valve regurgitation as an etiology of DAH. Acute mitral valve regurgitation can be a life-threatening condition and often requires urgent intervention. In rare cases, acute mitral regurgitation may result in a regurgitant jet which is directed towards the right upper pulmonary vein and may specifically cause right-sided pulmonary edema and right-sided DAH. Surgical repair of the mitral valve results in rapid resolution of DAH. Acute MR should be considered as a possible etiology in patients presenting with unilateral pulmonary edema, hemoptysis, and DAH.